2018
DOI: 10.2340/16501977-2373
|View full text |Cite
|
Sign up to set email alerts
|

Prediction for return to driving after the first-ever stroke in Korea: The KOSCO study

Abstract: Male patients, education about return to driving, lower mRS, and higher FMA at 7 days after stroke are predictors of return to driving. This model could be used by clinicians to help counsel patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…Among physical factors, stroke and lower extremity function were identified as predictors of DC. Stroke, as a neurologic problem, leads to decreases in visual field, attention and information processing speed and physical function, eventually causing stroke survivors to reduce or cease driving [ 41 , 42 ]. The results showed that older adults who had difficulty climbing stairs as an indicator of lower extremity function were 1.50 times more likely to stop driving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among physical factors, stroke and lower extremity function were identified as predictors of DC. Stroke, as a neurologic problem, leads to decreases in visual field, attention and information processing speed and physical function, eventually causing stroke survivors to reduce or cease driving [ 41 , 42 ]. The results showed that older adults who had difficulty climbing stairs as an indicator of lower extremity function were 1.50 times more likely to stop driving.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the assessment of physical function, such as lower extremity function, is required to determine the need for DC. However, in terms of stroke survivors, one study reported that 66.1% of patients with stroke returned to driving within one year after the stroke [ 42 ]. Another study reported that a continuous exercise rehabilitation program allowed stroke patients to recover their extremity function and driving ability [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obwohl es auch einige Studien gibt, die Vorhersagealgorithmen für die Kommunikation [4], Kognition [5], Depression [6], Rückkehr an den Arbeitsplatz [7] und Fahrtüchtigkeit [8] beleuchten, sind die Algorithmen für die Vorhersage der Erholung der Motorik nach Schlaganfall bisher am umfassendsten untersucht. Einen Überblick über diese Verfahren finden Sie in ▶ Tab.…”
Section: Prognose: Die Erholung Nach Schlaganfall Vorhersagenunclassified
“…Nevertheless, many stroke survivors return to driving. In the Republic of Korea, 66.1% of patients with first-ever stroke return to driving at a mean of 2.15 months after stroke [4]. It is essential to decide the returning time for stroke survivors since they are all different in the severity of residual symptoms and the degree of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, 30% to 43% of the approximately 6 million stroke survivors drive again within a year, and 87% of them return to driving without formal driving evaluation [18]. Furthermore, a relatively small percentage of stroke survivors (25.9%) received driving evaluations or advice before return to driving in the Republic of Korea [19]. Also, stroke patients themselves and their families tend to overestimate the driving performance of stroke survivors [20].…”
Section: Introductionmentioning
confidence: 99%